Applied geography: principles and practical application: (A study on Iraqi cities and governorates) - Mousa, Maitham (Al-Adab Journal, 2023)
The applied geographical approach has the ability to shed light on the nature and causes of a wide range of economic, social and environmental problems, and to develop appropriate solutions to them. and applied, as well as the concept of useful knowledge, and then this research is supplemented by empirical case study examples of applied research in the field of urban geography, with special reference to the main question of the quality of life and human well-being, finally we adopt a future perspective to address the question of the value of applied geography in contemporary society.